Viability of earthworm breeding for one, two and three months in soil treated with different concentrations of polluted water - Safaa Mahmoud; Adnan mohammed (College of Education for Pure Sciences, 2018)
This study is conducted to know the of effect of breeding earthworm for month , two month and three month in soil polluted with the concentration 25,50, 75, 100% of polluted water on its viability. The treatment reduce rate of specificgrowth ratio and it was 59.08 and 78.57% at the concentration 25 and75% respectively , also the treatment cause reducing in the weight of the treated earthworm and it was -0.079 and 0.0787 g at the concentration 25 and100%respectively. This study aimed to know the affect of this treatment on the worms death percentage , and also to knowing the percentage of protein body content... and showed that the polluted water affected thickness the body wall and epithelium of the digestive system and it´s caused the reduce thickness.